1992
DOI: 10.1051/limn/1992003
|View full text |Cite
|
Sign up to set email alerts
|

Structure et typologie ichtyenne de trois bras morts de la Garonne

Abstract: L'étude de la structure et de la typologie ichtyenne a été réalisée dans trois bras morts de la Garonne de 1988 à 1990. Les populations piscicoles ont été échantillonnées en utilisant deux méthodes de pêche complémentaires : l'Echantillonnage Ponctuel d'Abondance (E.P.A.) par pêche électrique et la pêche aux filets. Les échantillons obtenus par E.P.A. constituent la base de données principale pour cette étude.Les peuplements ichtyques de ces trois bras morts sont dominés par les cyprinidés et présentent une fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
7
0
4
Order By: Relevance
“…4). However, no drastic changes in fish composition have been recorded in the Garonne river basin, at least since the 1980s (Bengen et al 1992;Hutagalung 1998). Both the temporal variability of fish assemblages (Oberdorff et al 2001) and the location of sampling sites in the basin are other sources of community change that may explain atypical sites clustering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). However, no drastic changes in fish composition have been recorded in the Garonne river basin, at least since the 1980s (Bengen et al 1992;Hutagalung 1998). Both the temporal variability of fish assemblages (Oberdorff et al 2001) and the location of sampling sites in the basin are other sources of community change that may explain atypical sites clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Electrofishing surveys were made either by wading in shallow areas or by boat in the deeper reaches during low-flow periods (i.e., late summer). Moreover, local repeated surveys on some sampling sites showed that both environmental features and fish assemblages did not dramatically vary along the 10-year sampling period (Bengen et al 1992;Mastrorillo 1997;Hutagalung 1998;Cattanéo et al 1999;Reyjol 2002;Aguilar Ibarra 2004;P. This combination of methods allows an effective assessment of fish diversity in rivers (Seegert 2000), however, as abundance measures reflect collection intensity (Angermeier & Smogor 1995), only presence-absence data were considered in order to remove sampling bias as recommended by Hughes & Gammon (1987).…”
Section: Datamentioning
confidence: 96%
“…/ nr 2 ) at sta tions 2D, 3D and 4D have been taken in Prevot (1984). Data on the three other stations were obtained by eight collections with a rom net in morphodynamic condi tions characteristic of each station in the three seasons (Bengen et al 1992, Hutagalund et al 1997. Four fish sampling series per station (December 1994, March, June, September 1995 enabled the assessment of the structure of fish communities.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…L'abondance est de l'ordre de 10 ind./EPA en été et de l'ordre de 5 ind./EPA en hiver. Bengen et al (1992) avaient péché 3 bras morts de la Garonne et capturé en moyenne 11,7 ind./EPA, chiffre plus élevé que dans la présente étude mais obtenu sur des sites lentiques particulièrement riches en abris, très peuplés en alevins et en juvéniles.…”
Section: Abondanceunclassified